An event‐triggered approach to security control for networked systems using hybrid attack model - Liu, Jinliang; Wang, Yuda; Zha, Lijuan; Xie, Xiangpeng; Tian, Engang (International journal of robust and nonlinear control, 2021)
This article presents an event‐triggered approach to security control for networked systems by using hybrid attack model. Stochastic deception attacks, replay attacks, and denial of service attacks are assumed to occur in the communication network. The main contribution of the article is that an event‐triggered control strategy is presented to stabilize the networked systems based on the hybrid attacks and the network resource limitations. A novel event‐based model for networked control systems under hybrid attacks is established. Based on the proposed model, sufficient conditions are acquired to guarantee the closed‐loop system stability and the controller design method is developed. Finally, two simulation examples are given to validate the feasibility of the proposed method.